2018
DOI: 10.32598/bcn.9.6.389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Jobelyn® on Isoniazid-Induced Seizures, Biomarkers of Oxidative Stress and Glutamate Decarboxylase Activity in Mice

Abstract: Introduction:Isoniazid-induced seizure, often described as Status Epilepticus (SE), is an emergency condition characterized by repeated convulsive episodes that responds poorly to the currently available anticonvulsant drugs. The current study aimed at ascertaining the effect of Jobelyn® (JB), an African dietary supplement, on seizures, altered oxidative stress, and glutamate decarboxylase activity induced by isoniazid in mice.Methods:A total of 6 mice received JB (10–50 mg/kg, PO), pyridoxine (300 mg/kg), dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Isoniazid at high doses inhibits GABA synthesis and depletes the GABA contents of the brain. Consequently, this drug can induce seizures by inhibiting GABA transmission ( Asehinde et al, 2018 ; Patil et al, 2011 ). However, we used low doses of isoniazid that unlike the high doses can increase the GABA levels in the brain ( Perry & Hansen, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoniazid at high doses inhibits GABA synthesis and depletes the GABA contents of the brain. Consequently, this drug can induce seizures by inhibiting GABA transmission ( Asehinde et al, 2018 ; Patil et al, 2011 ). However, we used low doses of isoniazid that unlike the high doses can increase the GABA levels in the brain ( Perry & Hansen, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main mechanisms by which isoniazid influences the brain is the modulation of the GABAergic system. Research indicates that isoniazid in high doses decreases the GABA levels of the brain and induces convulsions ( Asehinde et al, 2018 ; Gupta, Dua, Kazmi, & Anwar, 2014 ; Patil, Patil, Patil, & Jadhav, 2011 ). However, some studies showed that low-dose isoniazid has GABA-elevating effects ( Perry & Hansen, 1973 ; Perry, Urquhart, Hansen, & Kennedy, 1974 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isoniazid-Induced Seizure Model. The method was as previously described [19]. Animals were adapted to the chamber for 1 h before receiving treatment with either CPE (30-300 mg/kg, p.o.…”
Section: Plant Collection and Extractionmentioning
confidence: 99%
“…It is necessary to create antiepileptic medicines (AEDs) that are more effective, safer, and have improved clinical characteristics. Status epilepticus (SE), also known as an isoniazidinduced seizure, is a serious disorder marked by frequent convulsive episodes that does not respond well to the currently available anticonvulsant drugs [5]. Status Epilepticus (SE) is one of the major side effects of isoniazid, a first line medication used for the treatment of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%